Status Perceraian Lembaga Kedamangan Adat Dayak Kecamatan Pahandut Kota Palangkaraya - Ilmi, Mifathul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2016)
Divorce in Kedamangan institution is a customary that must be done by the Dayak people. Divorce hearing at the Kedamangan institution is set in Central Kalimantan Provincial Regulation No. 16 of 2008 on Dayak local institution in Central Kalimantan. The local regulation explains that Kedamangan agency may issue a certificate of divorce. This research focuses on divorce status in the Kademangan institution of Pahandut, Palangkaraya. The data are collected through interview and observation and then analyzed with descriptive-inductive mindset. The status of divorce existing in Kedamangan institution cannot be categorized as a raj‟i nor ba‟in divorce since there is no certain regulation of iddah (waiting period for ex-wife to marry), so that reconciliation can be done at any time they want. The law used in Kedamangan institution is the Dayak Customary Law. In Islamic law, such divorce is legitimate because it has met the pillars and conditions of divorce. But the legal consequences of divorce in Kademangan institute is a little bit feared could lead to mafsadah. It is because there is no a clear determination about kind of divorce, reconciliation, and waiting period for a wife. Even, in a formal law, divorce at the Kademangan institutution remains invalid because it is not done in Religious Courts even has been legally regulated on the local regulation. [Perceraian di Lembaga Kedamangan merupakan perceraian adat yang wajib dilakukan oleh masyarakat adat Dayak. Sidang perceraian di Lembaga Kedamangan diatur dalam Peraturan Daerah Provinsi Kalimantan Tengah Nomor 16 tahun 2008 tentang Kelembagaan Adat Dayak di Kalimantan Tengah. Peraturan Daerah tersebut menjelaskan bahwa lembaga Kedamangan dapat mengeluarkan surat keterangan cerai. Tulisan ini mengkaji status perceraian di lembaga kedamangan adat Dayak Kecamatan Pahandut Kota Palangkaraya.Teknik pengumpulan data dilakukan melalui wawancara dan observasi kemudian dianalisis dengan metode deskriptif dengan pola pikir induktif. Status perceraian dari hasil putusan perceraian di Lembaga Kedamangan tidak dapat dikategorikan dalam jenis talak raj‟iy maupun talak bā‟in karena tidak adanya ketentuan „iddah bagi istri sehingga rujuk dapat dilakukan kapan pun. Landasan hukum yang digunakan di Lembaga Kedamangan adalah Undang-Undang Hukum Adat Dayak dari aturan nenek moyang. Menurut hukum Islam perceraian tersebut sah karena telah memenuhi rukun dan syarat perceraian, akan tetapi akibat hukum dari perceraian di Lembaga Kedamangan sedikit banyak dikhawatirkan dapat menimbulkan ke-maḍarat-an karena tidak adanya ketentuan jenis talak, rujuk, dan „iddah bagi istri. Sedangkan secara hukum formil, perceraian di Lembaga Kedamangan tetap tidak sah karena tidak dilakukan di Pengadilan Agama sekalipun telah diatur dalam Peraturan Daerah.]